ABSOLUTIST SOVEREIGNTY AND NATIONAL SOVEREIGNTY: THE ORIGINS OF THE NATION-STATE - Гайко, О. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The process of state formation of the modern type (nation-states), which represents the gradual transformation of the absolutist sovereignty to national sovereignty. It is focusing on the fact that the process of centralization of state power took place against the background of democratization of state power in the transition from the absolutist sovereignty to national sovereignty.